Encapsulation of troglitazone and AVE0991 by gelation microspheres promotes epithelial transformation of adipose-derived stem cells. (June 2020) - Tao, Ke; Bai, Xiaozhi; Zhang, Dongliang; Liu, Mengdong; Zhang, Yue; Han, Fu; Yang, Xuekang; Han, Juntao; Hu, Dahai
Abstract: Deformities in human soft tissue caused by trauma or burn present a difficult problem in plastic surgery. In this study, we encapsulated troglitazone and angiotensin 1-7 mimetic AVE0991 in gelation microspheres with the goal of inducing epithelial transformation for potential applications in tissue reconstruction. After troglitazone or AVE0991 were encapsulated to gelation microspheres, their release kinetics and bioactivity were examined. Surface morphology and diameter of the gelation microspheres were evaluated using light microscopy. The release of the drugs was assessed in the presence of human adipose-derived stem cells (ADSCs). Treatment with troglitazone microspheres increased cell viability and activated the β-catenin in ADSCs. Moreover, the AVE0991 microspheres also increased cell viability and C-myc expression of ADSCs. These results showed that troglitazone and AVE0991 microspheres promoted the activity of ADSCs. Furthermore, ADSCs were co-treated with troglitazone and AVE0991 microspheres. Western blot and immunofluorescent staining showed that co-treatment with troglitazone and AVE0991 microspheres elevated the expression of epithelialization associated protein CK14 in ADSCs. In conclusion, our findings indicate that microspheres with troglitazone and AVE0991 can significantly improve the viability and epithelialization of ADSCs, which provides a new approach for the construction of tissue-engineered skin. Highlights: Characteristics of gelatin microspheres. Effects of encapsulation of troglitazone on the activity of ADSCs. Effects of encapsulation of AVE0991 on the activity of ADSCs. Encapsulation of troglitazone and AVE0991 affect epithelial transformation of ADSCs.